Accelerating Sustainable Tourism through the Hexa Helix Model in Pati Regency - Said Nur Octavianto; Jarot Tri Bowo Santoso; Rachmadi, Moch Faizal; Adzim, Fauzul; Susanti, Eka (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Tourism is a key economic sector in Indonesia, significantly contributing to foreign exchange and national revenue. Developing a sustainable tourism strategy requires collaboration across academia, businesses, communities, government, media, and NGOs. However, one major challenge in Indonesia’s tourism sector is the lack of synergistic, comprehensive, and integrated stakeholder collaboration. To address this issue, this study aims to develop a sustainable tourism strategy for Pati Regency based on the hexa helix model, which emphasizes multi-stakeholder engagement in tourism destinations. Using a mixed-methods approach, this research incorporates qualitative methods—such as interviews, observations, and documentation—and a quantitative analysis through MACTOR (Matrix of Alliance, Conflicts, Tactics, Objectives, Recommendations) to map stakeholder interactions. Findings reveal a high level of alignment between the Youth, Sports, and Tourism Office (DINPORAPAR) and SMEs, scoring 21.7 on the convergence scale. The primary focus for sustainable development is on enhancing innovation and competitive ability, identified as the most influential objective.